Creating a Pedagogical Space that Fosters the (Re)Construction of Self Through Life Stories of Pre-Service English Language Teachers - Álvaro Hernán Quintero Polo (Asociación Colombiana de Profesores de Ingles, 2016)
People's true selves comprise a life story that may be considered as a narrative. With that idea in mind, the purpose of this article is to report on a pedagogical intervention that bridged life stories and a narrative perspective to examine nine, out of eighty, pre-service English language teachers' (re)construction of their true selves while engaged in a three-step introspective practice. Such (re)construction was manifested in written life stories which were interpreted and found to reveal these main themes: Meaningful Others in Shaping Their Self-as-Teacher, The Human Dimension in the Formation of Teachers of English, and Becoming Teachers of English Who Are Transformative, Instead of Transmissionists.